An assessment of The Capacity Drops at The Bottleneck Segments: A review on the existing methodologies - Sugiarto Sugiarto; . Lulusi; Sofyan M. Saleh (Graduate Program of Syiah Kuala University, 2015)
The term of capacity is very useful to quantify the ability of transport facilities in terms of carrying traffic. The capacity of the road is an essential ingredient in the planning, design, and operation of roadways. It is desirable for traffic analyst to be able to predict the time and places where congestion will occur and the volumes to be expected. Most of urbanized areas have been experiencing of traffic congestion problems particularly at urban arterial systems. High traffic demand and limited supply of roadways are always the main factors produced traffic congestion. However, there are other sources of local and temporal congestion, such as uncontrolled access point, median opening and on-street parking activities, which are caused a reduction of roadway capacity during peak operations. Those locations could result in reduction of travel speed and road, as known as hidden bottlenecks. This is bottleneck which is without any changes in geometric of the segments. The Indonesian Highway Capacity Manual (IHCM, 1997) is used to assess urban arterial systems till current days. IHCM provides a static method for examining the capacityand does not systematically take into account of bottleneck activities. However, bottleneck activities create interruption smooth traffic flow along arterial streets, which in turns stimulate related problems, such as, excessive air pollution, additional energy consumption and driver’s frustration due to traffic jammed. This condition could happen simultaneously; mostly repetitive and predictable in same peak hour demands. Therefore, this paper carefully summarize on the existing methodologies considering required data, handled data processing and expected output of each proposed of analysis. We further notice that dynamic approach could be more appropriated for analyzing temporal congestion segments (median opening, on street parking, etc.). Method of oblique cumulative plot seems to be more applicable in terms of convenient, surveying tool and the accuracy of analysis. This method is easy to handle and powerful in identifying flow and speed fluctuations during breakdown occurs